Evaluasi Administrasi Pelaksanaan Pemilu Serentak 2019 Terhadap Nilai-Nilai Pancasila - Lita Tyesta ALW (Administrative Law and Governance Journal, 2019)
Abstract The aim of this paper is to find out the administrative evaluation of the implementation of simultaneous elections in 2019 on the actualization of the values of Pancasila. Writing is an ingredient in the framework of participation in Focus Groups Discussion with the theme "Evaluation of the Implementation of the 2017 Election Law Against the Values of Pancasila" held by BPIP, Jakarta 5 to 7 August 2019, and arranged using the conceptual approach and factual approach. The results of the study indicate that the implementation of general elections in the future must be more planned and well-programmed so that things that become weaknesses in the simultaneous elections in 2019 do not occur. In the future, simultaneous elections must be carried out including: separating national and local elections; there must be an improvement in the recruitment and time management model especially for the organizers; Preparation of the final voter list should be cross-institutional related to population; A review of the provisions of the Presidential Threshold is required if the General Elections are still held simultaneously; Time management in the preparation of ballot distribution to the most remote, remote, most challenging, outermost areas, so that voting can be done simultaneously, including at the time of collection for ballot counting, and; Development of an accurate and trusted information technology system in the vote-counting process. Keywords: Administrative Evaluation, Election Implementation, Pancasila Values, Abstrak  Tulisan bertujuan untuk mengetahui evaluasi administrasi pelaksanaan pemilu serentak tahun 2019 terhadap aktualisasi nilai nilai pancasila. Penulisan merupakan bahan dalam rangka keikutsertaan pada Focus Groups Discussion dengan tema “Evaluasi Implementasi UU Pemilu Tahun 2017 Terhadap Nilai-Nilai Pancasila“ yang diselenggarakan oleh BPIP, Jakarta 5 sampai dengan tanggal 7 Agustus 2019, dan disusun menggunakan pendekatan conceptual approach dan Factual Approach. Hasil kajian menunjukan bahwa pelaksanaan pemilihan umum ke depan harus lebih terencana dan terprogram dengan baik agar hal hal yang menjadi kelemahan pelaksanaan pemilu serentak tahun 2019 tidak terjadi. Kedepan pemilu serentak harus melakukan diantaranya: memisahkan Pemilu tingkat pusat dan tingkat daerah; harus dilakukan perbaikan model perekrutan dan manajemen waktu khususnya bagi penyelenggara; Penyusunan daftar pemilih tetap sebaiknya lintas institusi terkait kependudukan; Wajib dilakukan tinjau ulang ketentuan  Presidential  Treshold apabila Pemilu  tetap dilaksanakan secara serentak; Manajemen waktu pada persiapan distribusi surat suara ke pelosok, wilayah terjauh, terpencil, tersulit, terluar, sehingga pemungutan suara dapat dilakukan serentak waktunya, termasuk pada saat pengumpulan untuk penghitungan surat suara, dan; Pengembangan sistem teknologi informasi  yang akurat dan terpercaya dalam proses penghitungan suara. Kata Kunci: Evaluasi Administratif, Pelaksanaan Pemilu, Nilai Nilai Pancasila,